Overinhibition of corticostriatal activity following prenatal cocaine exposure. Issue 3 (7th December 2012) - Wang, Wengang; Nitulescu, Ioana; Lewis, Justin S.; Lemos, Julia C.; Bamford, Ian J.; Posielski, Natasza M.; Storey, Granville P.; Phillips, Paul E. M.; Bamford, Nigel S.
<x xml:space="preserve">Abstract</x> Objective Prenatal cocaine exposure (PCE) can cause persistent neuropsychological and motor abnormalities in affected children, but the physiological consequences of PCE remain unclear. Conclusions drawn from clinical studies can sometimes be confounded by polysubstance abuse and nutritional deprivation. However, existing observations suggest that cocaine exposure in utero, as in adults, increases synaptic dopamine and promotes enduring dopamine‐dependent plasticity at striatal synapses, altering behaviors and basal ganglia function. Methods We used a combination of behavioral measures, electrophysiology, optical imaging, and biochemical and electrochemical recordings to examine corticostriatal activity in adolescent mice exposed to cocaine in utero. Results We show that PCE caused abnormal dopamine‐dependent behaviors, including heightened excitation following stress and blunted locomotor augmentation after repeated treatment with amphetamine. These abnormal behaviors were consistent with abnormal γ‐aminobutyric acid (GABA) interneuron function, which promoted a reversible depression in corticostriatal activity. PCE hyperpolarized and reduced tonic GABA currents in both fast‐spiking and persistent low‐threshold spiking type GABA interneurons to increase tonic inhibition at GABAB receptors on presynaptic corticostriatal terminals. Although D2 receptors paradoxically increased glutamate release following PCE, normal corticostriatal modulation by dopamine was reestablished with a GABAA receptor antagonist. Interpretation The dynamic alterations at corticostriatal synapses that occur in response to PCE parallel the reported effects of repeated psychostimulants in mature animals, but differ in being specifically generated through GABAergic mechanisms. Our results indicate approaches that normalize GABA and D2 receptor‐dependent synaptic plasticity may be useful for treating the behavioral effects of PCE and other developmental disorders that are generated through abnormal GABAergic signaling. ANN NEUROL 2013;73:355–369